ABYSSINIAN MIGRATION: A Model of Inter-religious Co-existence of Early Islam Based on Dialogue in Relation to Second Vatican Council’s Document Nostra Aetate - Vettikuzhiyil, Roy Joseph; Singgih, Emanuel Gerrit; Wahid, Abdul (Asian Horizons, 2019)
We are living in a pluralistic society where many religions and beliefs are mingled extensively. It is important for us to live in harmony with other religions in the world. This paper aims at analysing the historical Islamic migration to Abyssinia, a Christian country, which took place in 615 AD. The Abyssinian model is helpful in moulding an interreligious harmonious life. Through this paper, we have made an attempt to connect Abyssinian migration and the dialogical process which led to safe co-existence of Muslims in Abyssinia with the Catholic Church’s concept of interreligious life based on Second Vatican Council’s document on the relationship of Church to Non- Christian religions (Nostra Aetate). The common factor which binds both Christians and Islam is analysed and made as a base for further development. The emphasis on the concept of ‘ray of truth’ in other religions in the Second Vatican Council is also examined in the context of Abyssinian migration. The paper ends with the Second Vatican Council’s plea for promoting and safeguarding the values like social justice, moral values, peace and freedom for a better tomorrow. Being the largest and second largest religions in the world, Christianity and Islam can contribute a lot to the world through its peace building by mutual dialogue and co-existence. If we take these examples seriously into account, then a multi-religious pluralistic society is possible.